Failure of a stability conjecture in general relativity - Gurtug, O; Halilsoy, M (Editrice Compositori Bologna, 2002)
By employing an exact back-reaction geometry, Helliwell-Konkowski stability conjecture is shown to fail. This happens when a test null dust is inserted into the interaction region of cross-polarized Bell-Szekeres space-time.
Keywords: Colliding Waves; Cauchy Horizons